Strategic Intelligence Analysis in Monitoring Efforts on Potential Misuse of Commercial Explosives - Navy Pradhana Primasatya; Arthur Josias Simon Runturambi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discusses the efforts of the POLRI Intellegence Division in carrying out the role of supervision and control related to the misuse of the function of commercial explosives for the remaining commercial explosives through strategic intelligence analysis. This study uses a qualitative method that begins with a descriptive approach to analyze the existing conflict. The theories and concepts used are strategic intelligence analysis and security intelligence theory. This study analyzes the monitoring efforts to prevent the misuse of commercial explosives functions and the problems of the presence of commercial explosive residues. The results of research related to regulations show that there is a debate about the effectiveness of policies, regulations, and the proposed establishment of a Law on Commercial Explosives. In addition, the governance structure shows that there are problems regarding the weakness of the supervisory mechanism, low capacity of employees, and weak coordination, as well as the formulation of the Supervisory Agency as a substitute for the Explosives Supervisory Team.Strategic Intelligence Analysis in Monitoring Efforts on Potential Misuse of Commercial Explosives